Cryptographic File System for Secured Group Communication - Blessy Pau, V; Jibi K, George (International Journal of Computer Sciences and Engineering, 2015)
Cloud computing is the delivery of computing and storage capacity as a service to users. The cloud has huge potential when it comes to storing, sharing and exchanging files, but the security provided by cloud services is questionable. Users, after uploading their files, have no control anymore about the way their data is handled and the location where it is stored. Considering both corporate and personal data which is often secret and sensitive in nature, one should not blindly entrust it to a cloud storage provider. In order to ensure the confidentiality of date during transferring it to the cloud storage, we need some encryption techniques. In this paper, we present a cryptographic file system based on Multiple-Key Public-Key Cryptography which is designed for enhancing the cloud data storage security for an organization. Here, files are encrypted by the administrator of the organization before they are uploaded to the cloud storage providers. Therefore, the cloud storage providers can’t access the users’ data. This encryption technique also allows the sharing files within a group of users of an organization. A key feature is that it handles changes in group membership and modification of files in an extremely efficient manner, by using the same encryption method.